EVALUATIVE COLLOCATIONS AND STANCE IN TRILINGUAL MEDIA CORPORA: A PILOT STUDY OF ENGLISH, RUSSIAN, AND UZBEK NEWS HEADLINES (Eureka Journal of Education & Learning Technologies, 2026)
This article examines how evaluative meaning is compressed into short news headlines across English, Russian, and Uzbek media discourse. Rather than treating headlines as neutral labels, the study approaches them as dense sites of stance, framing, and audience positioning. A small pilot corpus of 360 online headlines was assembled for methodological demonstration, with 120 headlines in each language and three thematic clusters: politics, economy, and emergency reporting. The analysis combines frequency observation, collocational reading, and close comparison of recurrent stance markers such as crisis labels, attribution verbs, hedging devices, and backgrounding patterns. The results show that all three languages rely on compact evaluation, but they do so through somewhat different preferences. English headlines favor compressed noun phrases and risk-oriented framing; Russian headlines show a higher rate of explicit attribution and contextual framing; Uzbek headlines more often balance institutional neutrality with indirect evaluation through lexical pairing and source-based wording. Because the corpus is small and purposively built, the findings are exploratory. Even so, the study demonstrates that corpus-assisted headline analysis can reveal not only what media texts say, but also how they guide readers toward a preferred
Keywords: Media discourse, corpus linguistics, collocation, news headlines, stance, trilingual analysis.